PENINGKATAN EFISIENSI PROSES PENGERINGAN KAYU DAN BLOK PUPUK MENGGUNAKAN PENGERING BERBASIS SIKLUS KOMPRESI UAP - Petrus Kanisius Purwadi; FA Rusdi Sambada; Iswanjono Iswanjono; Budi Sugiharto; Yosef Agung Cahyanta; Wibowo Kusbandono (Universitas Sanata Dharma, 2022)
The wood-furniture drying process in the industry using wood fuel is deemed inefficient, wasteful, takes a long time, is unsafe, impractical, and not environmentally friendly. Furthermore, the process of drying fertilizer blocks with the sun, apart from requiring a large area of land, also cannot be carried out in the rainy season. This service is carried out in two industrial partners, namely CV Nuansa Kayu Bekas in Sragen and PT Wira Cahya Pratama in Klaten. This service aims to increase understanding of an effective drying machine for the drying process of wood furniture and block-fertilizer in the industry by using a vapour compression cycle. In addition, to increase productivity and profits in the industry. The training venues are conducted in the industries of the two partners. Activities in this service include training on drying machines and assistance in the manufacture, operation and maintenance of effective dryers, especially for the wood-furniture and fertilizer-block industries. The implementation of the service has been going well and smoothly. The outputs produced are activity videos, publications in Suara Merdeka newspaper, Jogja Daily and the Sanata Dharma University website, service articles published in service journals, and Partner satisfaction surveys.